Secondary Variants in Individuals Undergoing Exome Sequencing: Screening of 572 Individuals Identifies High-Penetrance Mutations in Cancer-Susceptibility Genes - Johnston, Jennifer J.; Rubinstein, Wendy S.; Facio, Flavia M.; Ng, David; Singh, Larry N.; Teer, Jamie K.; Mullikin, James C.; Biesecker, Leslie G. (American journal of human genetics, 2012)
Genome- and exome-sequencing costs are continuing to fall, and many individuals are undergoing these assessments as research participants and patients. The issue of secondary (so-called incidental) findings in exome analysis is controversial, and data are needed on methods of detection and their frequency. We piloted secondary variant detection by analyzing exomes for mutations in cancer-susceptibility syndromes in subjects ascertained for atherosclerosis phenotypes. We performed exome sequencing on 572 ClinSeq participants, and in 37 genes, we interpreted variants that cause high-penetrance cancer syndromes by using an algorithm that filtered results on the basis of mutation type, quality, and frequency and that filtered mutation-database entries on the basis of defined categories of causation. We identified 454 sequence variants that differed from the human reference. Exclusions were made on the basis of sequence quality (26 variants) and high frequency in the cohort (77 variants) or dbSNP (17 variants), leaving 334 variants of potential clinical importance. These were further filtered on the basis of curation of literature reports. Seven participants, four of whom were of Ashkenazi Jewish descent and three of whom did not meet family-history-based referral criteria, had deleterious BRCA1 or BRCA2 mutations. One participant had a deleterious SDHC mutation, which causes paragangliomas. Exome sequencing, coupled with multidisciplinary interpretation, detected clinically important mutations in cancer-susceptibility genes; four of such mutations were in individuals without a significant family history of disease. We conclude that secondary variants of high clinical importance will be detected at an appreciable frequency in exomes, and we suggest that priority be given to the development of more efficient modes of interpretation with trials in larger patient groups.